2019
DOI: 10.1038/s41467-019-13229-8
|View full text |Cite
|
Sign up to set email alerts
|

AMPA receptors in the synapse turnover by monomer diffusion

Abstract: The number and subunit compositions of AMPA receptors (AMPARs), hetero- or homotetramers composed of four subunits GluA1–4, in the synapse is carefully tuned to sustain basic synaptic activity. This enables stimulation-induced synaptic plasticity, which is central to learning and memory. The AMPAR tetramers have been widely believed to be stable from their formation in the endoplasmic reticulum until their proteolytic decomposition. However, by observing GluA1 and GluA2 at the level of single molecules, we fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 69 publications
1
25
0
Order By: Relevance
“…Another factor to take into account when analyzing AMPAR exchanges lies in the stability of the tetramers once inserted in the membrane. A study that uses single molecule imaging has reported that AMPAR membrane tetramers would be metastable complexes that are in dynamic equilibrium with their respective monomers and dimers ( Morise et al, 2019 ). This would imply dissociations of the AMPARs that allow changes in subunit composition at a very fast rate.…”
Section: Memory Retrieval and Ampar Subunits: A Matter Of Timingmentioning
confidence: 99%
“…Another factor to take into account when analyzing AMPAR exchanges lies in the stability of the tetramers once inserted in the membrane. A study that uses single molecule imaging has reported that AMPAR membrane tetramers would be metastable complexes that are in dynamic equilibrium with their respective monomers and dimers ( Morise et al, 2019 ). This would imply dissociations of the AMPARs that allow changes in subunit composition at a very fast rate.…”
Section: Memory Retrieval and Ampar Subunits: A Matter Of Timingmentioning
confidence: 99%
“…We wonder whether it is such GluN1/GluN2 heterodimers, or even GluN1 monomers themselves (see [56]) that are responsible for the non-ionotropic signalling described above. This explanation may appear fanciful but recent data suggest that AMPARs are in fact 'metastable' within the plasma membrane and can quickly transition to monomers and dimers, only to readily form tetramers again [57]. The exclusion of NMDAR ionotropic function removes the requirement for a tetrameric structure, so it is not unreasonable to consider that NMDAR subunits, existing as monomers or heterodimers on the cell surface could signal via the non-ionotropic transmembrane conformational change as one would conceive for a heterotetrameric NMDAR.…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…In addition, although AMPAR has been thought to be present as a tetramer ( Greger et al, 2007 ), recent observations of SPT have shown that the majority of diffusive AMPARs are monomers or dimers ( Morise et al, 2019 ). Molecular diffusion in the monomer form increases an exchange rate between the inside and the outside of PSDs, making it possible to efficiently change the AMPAR composition within synapses.…”
Section: Molecular Crowding In the Psdmentioning
confidence: 99%